2007
DOI: 10.1264/jsme2.22.128
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Predominant Bacteria in a Microbial Consortium Cultured on Media Containing Aromatic and Saturated Hydrocarbons as the Sole Carbon Source

Abstract: A No.22 consortium was isolated from contaminated soils at oilfields by repeated transfer on a mineral salts medium with the aromatic hydrocarbon fraction from crude petroleum. The consortium was able to degrade aromatic hydrocarbons at high rates. Fourteen major DNA bands were detected in the consortium by PCR-DGGE. Three strains were capable of forming colonies on agarose plates containing mineral salts and aromatic hydrocarbons, and identified as Pandoraea sp. Y1, Hyphomicrobium facile Y3, and Burkholderia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Growth and COD removal by indigenous bacterial isolates on NORWW. Similar biodegradation potentials on crude oil[32] and other hydrocarbon contaminated sites[33] [34] were reported for indigenous microorganisms but with much lower rates. Addition of nitrogen and phosphorus during enrichment process might have played an important role in acceleration of biodegradation in the present study.…”
supporting
confidence: 69%
“…Growth and COD removal by indigenous bacterial isolates on NORWW. Similar biodegradation potentials on crude oil[32] and other hydrocarbon contaminated sites[33] [34] were reported for indigenous microorganisms but with much lower rates. Addition of nitrogen and phosphorus during enrichment process might have played an important role in acceleration of biodegradation in the present study.…”
supporting
confidence: 69%
“…Therefore, a microbial consortium containing a number of microorganisms which synthesize the degradative enzymes for different parts of the decomposition pathway is considered to be well suited to the degradation of aromatic hydrocarbons. Microorganisms not directly involved in the degradation process also probably play a role by producing micronutrients or surface-active agents for the solubilization of aromatic hydrocarbons [13,22]. Sugiura et al [23] reported that biodegradation caused by mixed cultures was more effective than that caused by pure cultures mainly due to the complexity of oil products.…”
Section: Discussionmentioning
confidence: 99%
“…(including some pathogenic ones) were isolated from environmental samples such as soils, hen dung, and oxic water layer above a sulfide-containing sediment ( Coenye et al, 2000 ; Anandham et al, 2010 ; Sahin et al, 2011 ). These free-living species participate in the biodegradation of various organic substances (including important pollutants) or perform chemosynthesis by oxidation of heterotrophic sulfur ( Okeke et al, 2002 ; Graff and Stubner, 2003 ; Ozaki et al, 2007 ; Liz et al, 2009 ; Kumar et al, 2015 ; Jeong et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%